All males are not created equal: Fertility differences depend on gamete recognition polymorphisms in sea urchins - Palumbi, Stephen R. (The National Academy of Sciences, 1999)
Behaviors, morphologies, and genetic loci directly involved in reproduction have been increasingly shown to be polymorphic within populations. Explaining how such variants are maintained by selection is crucial to understanding the genetic basis of fertility differences, but direct tests of how alleles at reproductive loci affect fertility are rare. In the sea urchin genus Echinometra, the protein bindin mediates sperm attachment to eggs, evolves quickly, and is polymorphic within species. Eggs exposed to experimental sperm mixtures show strong discrimination on the basis of the males’ bindin genotype. Different females produce eggs that nonrandomly select sperm from different males, showing that variable egg–sperm interactions determine fertility. Eggs select sperm with a bindin genotype similar to their own, suggesting strong linkage between female choice and male trait loci. These experiments demonstrate that alleles at a single locus can have a strong effect on fertilization and that reproductive loci may retain functional polymorphisms through epistatic interactions between male and female traits. They also suggest that positive selection at gamete recognition loci like bindin involves strong selection within species on mate choice interactions.